Ibrutinib in the Treatment of Refractory Chronic Lymphocytic Leukemia - EA Nikitin; EA Dmitrieva; MA Panteleev; EI Emelina; VL Ivanova; YuB Kochkareva; EG Arshanskaya; IE Lazarev; EE Markova; LA Mukha; NG Novitskaya; MM Pankrashkina; et al. (Клиническая онкогематология)
Background & Aims. This paper presents the results of the observational study of ibrutinib in patients with chronic lymphocytic leukemia (CLL), conducted in SP Botkin Municipal Clinical Hospital. The main objective was the analysis of complications of ibrutinib and identification of factors, influencing the dosage regimen; the secondary objective was the estimation of the total response to treatment, event-free and overall survival.